PURWARUPA SISTEM FIRE DETECTOR BERBASIS ARDUINO UNO DENGAN INTEGRASI WEBSITE - , ALBERTUS GALIH P K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Prototype of fire detector based web integration Arduino UNO is created based on the number of catastrophic fires that may arise from trivial things that can cause a loss of material (buildings and household furnishings), psychological and even fatalities. This prototype is designed to detect a fire in a room, which consists of LM35DZ Temperature Sensor, Gas Sensor MQ-135, Arduino UNO microcontroller, Ethernet Shield W5100 module and adapter as the power supply. Then, the temperature sensor will detect the ambient temperature of the room (in units â° C) and gas sensors to detect gases that are around the room, especially carbon monoxide (in units of percent). When both temperature and gas sensor detects a certain amount, it will be compared to the set point that has been set on the Arduino Uno microcontroller. If the results of the both sensor measurement is smaller than the set point, then there is no warning display. But if the results of the both sensor measurement is larger than the set point, it will display a warning. Warning will be displayed in the web using the Ethernet Shield W5100 module support via a LAN connection. The display on the web, in the form of a warning \"BAHAYA\". So when the measurement is greater than the set point, may be possible in case of fire in the room. During the research, the authors found several conclusions : First, this prototype can work well in the room. Second, the difference comparison between LM35 temperature with a thermometer stem is 0.18 â° C. Third, more and more objects are burned, the combustion temperature is also higher. Fourth, high-measurement results which will affect the value correction. Fifth, MQ-135 gas sensor is a sensor to control the air quality control, so sensitive to some types of gas. Sixth, based on the research results, this device has been created to give a warning to the presence of fire.